APPLICATION OF HEALTH PROMOTION MODEL FOR BETTER SELF-CARE BEHAVIOR IN PATIENTS WITH DIABETES MELLITUS - Made Mahaguna Putra; Kusnanto Kusnanto; Candra Panji Asmoro; Tintin Sukartini (Belitung Raya Foundation, Indonesia, 2019)
Background: Diabetes mellitus (DM) is a major health problem in the world. DM patients should be able to perform self-care behavior. Diabetic self-care behavior is an effective strategy for controlling diabetes. Objective: The purpose of this study was to examine a health promotion model in patients with type 2 diabetes mellitus. Methods: A cross-sectional design was used, which involved 177 patients with type 2 diabetes from primary health care in Denpasar Bali Indonesia with a stratified random sampling. Independent variables were personal factors (age, sex, education, body mass index, socioeconomic status, self-motivation, illness perception, and belief), self-efficacy, and family support. The dependent variable was self-care behavior. A structural equation model was used to confirm the hypothesis model. Results: Personal factors (education, socioeconomic, and perceptions) (t = 2.891) and family support (t = 5.746) were associated with self-care behavior. Self-efficacy did not affect self-care behavior (t = .139). Conclusion: Diabetes self-care behavior is influenced by socioeconomic status, level of education, perception of the illness, and family support. Therefore, it is suggested for nurses to apply the health promotion model approach to increase self-care behavior of patients with type 2 diabetes mellitus.